Rice ASR1 and ASR5 are complementary transcription factors regulating aluminium responsive genes. (14th December 2015) - Arenhart, Rafael Augusto; Schunemann, Mariana; Bucker Neto, Lauro; Margis, Rogerio; Wang, Zhi‐Yong; Margis‐Pinheiro, Marcia
Abstract: Rice is the most tolerant staple crop to aluminium (Al) toxicity, which is a limiting stress for grain production worldwide. This Al tolerance is the result of combined mechanisms that are triggered in part by the transcription factor ASR5 . ASRs are dual target proteins that participate as chaperones in the cytoplasm and as transcription factors in the nucleus. Moreover, these proteins respond to biotic and abiotic stresses, including salt, drought and Al. Rice plants with silenced ASR genes are highly sensitive to Al. ASR5, a well‐characterized protein, binds to specific cis elements in Al responsive genes and regulates their expression. Because the Al sensitive phenotype found in silenced rice plants could be due to the mutual silencing of ASR1 and ASR5, we investigated the effect of the specific silencing of ASR5 . Plants with artificial microRNA silencing of ASR5 present a non‐transformed phenotype in response to Al because of the induction of ASR1 . ASR1 has the same subcellular localization as ASR5, binds to ASR5 cis‐regulatory elements, regulates ASR5 regulated genes in a non‐preferential manner and might replace ASR5 under certain conditions. Our results indicate that ASR1 and ASR5 act in concert and complementarily to regulate gene expression in response to Al. Abstract : Aluminium (Al) is a high abundant metal in earth's crust but presents mostly in nontoxic forms. Its solubilization occurs in acid soils, a major worldwide problem, because most arable land in the world have pH under 5.0. Although rice is considered one of the most tolerant crop to aluminium, the basis of this tolerance is still poorly understood, and only a few genes have been characterized until now. ASR genes constitute an intriguing gene family that respond to various stress conditions and is also regulated during plant development and may act as chaperones or as transcription factors. Recently, we showed that ASR5 transcript levels increase in response to Al and the silencing of this gene produced rice plants sensitive to Al (Arenhart et al. 2012 – Plant Cell and Environment). We also showed that ASR5 plays a key role in protecting plant in response to Al by regulating genes, which expression increased resistance to Al toxicity (Arenhart et al. 2014 – Molecular Plant). In the present manuscript, we show that not only ASR5 but also ASR1 act in concert and complementarily to regulate gene expression in response to Al. We also demonstrate that ASR5 and ASR1 suffer auto‐regulation in a possible positive feedback mechanism.